Mycoplasma Infection in Human Pathology and the Role of Antibacterial Drugs - A. A. Khryanin; O. V. Reshetnikov (Антибиотики и Химиотерапия)
The article highlights current issues of classification, pathogenesis, laboratory diagnosis, and treatment of mycoplasma infection of the urogenital tract (M.hominis, U.urealyticum). Authors present the data on the role of infection in the development of nongonococcal urethritis and infertility in men, as well as impaired reproductive function and adverse pregnancy outcomes in women. The article describes indications and laboratory diagnostic methods and lists the criteria for the appointment of antibiotic therapy, as well as the most preferred drugs.